Some theorems on the class M-A(n*) operators on Hilbert space - Al-shakarchi, Shaymaa (International Journal of Scientific Research and Management (IJSRM), 2024)
This work proves that if T belong to the class M-A(n*) operator and S* is an invertible operator belonging to the same class such that TX=XS, then T*X=XS*, where X is a Hilbert-Schmidt operator.